'Salting': preserving, seasoning, savouring, purifying and transforming through 'marine adventuring'. Issue 2 (3rd April 2019) - Morgan, Alun D.
ABSTRACT: This article explores, from a personal perspective, ageing and adventure in the context of the outdoor environment. Employing an autoethnographic sensibility, and drawing on fields of positive psychology, life course development, Outdoor and Adventurous Learning, and leisure studies, the paper discusses a range of motivations that contribute to my personal pursuit of a 'fulfilled life' now and in the future through 'marine adventuring'. Adventuring is used to refer to my engagement with challenging physical outdoor activities; but also to my pursuit of learning; and, moreover, in my 'existential' quest for meaning. The specific activities under consideration are: seakayaking, SCUBA-diving and sailing.